Systematic review of ratios between disease /health periodontitis modulators and meta-analysis of their levels in gingival tissue and biological fluids - Caldeira, François Isnaldo Dias; Hidalgo, Marco Antonio Rimachi [UNESP]; De Carli Dias, Marina Lara; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Pigossi, Suzane Cristina (Elsevier, 2021)
Objective: The ratio between molecules which acts towards the diseased or healthy phenotype determine whether the periodontitis lesions will progress or stabilize. Considering gingival tissue and biofluids, we aimed to present a systematic review (qualitative analysis) on the ratios between disease/health periodontitis modulators, and a meta-analysis (quantitative analysis) of their levels in individuals with periodontitis compared to controls. Design: Electronic searches of the PubMed, Scopus, EMBASE and Web of Science databases were conducted for publications up to May 2020. Results: A total of 53 publications were included in the systematic review, being 22 of them focusing on the ratios between Interleukin [IL]-1/IL-10, IL-6/IL-10, IL-1/IL-1RA and RANKL/OPG. Twenty-one publications were eligible for meta-analyses. The ratios of IL-1, IL-6 and RANKL mRNA levels were significantly higher in diseased gingival tissue, as well as their protein levels in gingival crevicular fluid (GCF) of periodontitis individuals. Considering the saliva levels, the RANKL/OPG ratio was higher in periodontitis subjects in comparison to controls. Meta-analyses showed higher IL-1β, IL-1α, IL-6 and IL-10 gene expressions in gingival tissue and protein levels in GCF, while RANKL was higher in GCF of periodontitis individuals in comparison to controls. Conclusions: Both the ratios and meta-analyses showed higher levels of modulators in gingival tissue and GCF of diseased individuals.
Keywords: Adaptive immunity; Cytokines; Immunity; Innate; Periodontitis